The Career Programmer Guerilla Tactics for an Imperfect World - Duncan, Christopher (Apress : Imprint: Apress, 2006)
Unrealistic schedules, unstable releases, continual overtime, and skyrocketing stress levels are legendary in the software development industry. Unlike traditional occupations such as accounting or administration, the software business is populated with programmers who are as creative and passionate about their work as musicians and artists. But for most programmers and project managers, it is a complete surprise when they enter the business world and find that internal politics, inept management, and unrealistic marketing drive the process, rather than a structured and orderly approach based on technical issues and quality. This guide, delivered with the wit and aplomb to make a serious topic entertaining and palatable, will help you survive the programming industry. The Career Programmer explains how you can work within the existing system to solve deadline problems and regain control of the development process. Youll master self-defense techniques to shield yourself, your project, and your code from corporate politics, arbitrary management decisions, and marketing-driven deadlines. Author Chris Duncan provides proven, practical, hands-on solutions designed to work even when tested by the political and chaotic realities of the business environment. Issues are addressed from the points of view of both the programmer and project manager, and steps are illustrated from all perspectivesfrom large-scale teams down to projects with a single developer. For you, the end results will mean less overtime and stress, higher-quality software, and a more satisfying career.